FORMULATION OF LEGAL PROVISIONS PROHIBITING MONEY POLITICS IN ELECTIONS: TOWARDS HONEST AND FAIR ELECTIONS - Pujiono, Pujiono; Prasetyoningsih, Nanik (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
The formulation of legal provisions prohibiting money politics in elections is a crucial step towards creating honest and fair elections. We must comprehend the boundaries of money politics, the kinds of actions that fall under its purview, and the efficacy of the penalties we can apply to those who violate them. In the context of elections, money politics refers to the practice or phenomenon where individuals use money as a tool to influence or win the outcome of an election. One of the main influences of money politics is to turn the election process into a vote-buying event, where voters who receive money or other material gifts tend to vote for candidates who offer these rewards, not based on ideological considerations or actual candidate qualifications. In Indonesia, the use of money politics in election practices has become a serious concern in society. Despite the prevalence of money crimes in elections, many remain unarrested and unpunished. The need for legal reform emphasizes the importance of strong legal and enforcement mechanisms to combat money politics. To prohibit the practice of money politics, there needs to be firmer and more effective legal provisions.